English Speaking Instructional Model for the 8th Grade Students: A Single Case Study at SMPN 2 Blitar - Sofansyah, Nurma Atalsa; Supriyono; Aini, Miza Rahmatika (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
English speaking has become a central focus in public school language instruction as a response to the increasing demand for global communication skills. To improve students' speaking proficiency, various instructional models have been implemented, one of which is the English-Speaking Instructional Model. This study aims to investigate how the model is applied to eighth-grade students at SMPN 2 Blitar. Employing a qualitative descriptive research design, data were collected through classroom observations, teacher interviews, and documentation analysis. The findings indicate that English teachers utilized instructional approaches such as ICARE (Introduction, Connect, Apply, Reflect, Extend) and Project-Based Learning to promote student engagement in communicative tasks. These tasks were carefully structured based on the annual and semester teaching plan, in alignment with the Merdeka Curriculum's emphasis on student-centered learning. Additionally, teachers integrated various digital and printed resources, including materials from the Internet and official platforms provided by the Ministry of Education to enrich the teaching and learning process. The study concludes that the effective application of this model, supported by appropriate instructional planning and resource selection, plays a significant role in enhancing students’ speaking abilities. It also underscores the need for ongoing teacher development to support innovative and adaptive English language instruction.